Étude Des Aspects Épidémiologiques Du Choléra Dans Le District De Santé De Tcholliré (Nord- Cameroun) - Ndié, Justin; Bayoro, Isaac; Takoukam, Isidore; Wina, Paul (European Scientific Journal, ESJ, 2016)
Cholera evolves in an endemo-epidemic mode in developing countries. In Cameroon, because of the weakness of our health system, mainly of the epidemiologic surveillance and inadequate timely response, many localities in our country are faced with intermittent cholera epidemics. This study was aimed at analyzing the epidemiological aspects of cholera in the Tcholliré Health District (North Region-Cameroon) in 2011. We therefore applied a retrospective cross-sectional study using data on cholera cases registered within the 27th and the 40th epidemiological weeks in the Tcholliré Health District in 2011. All patients infected with cholera were included. The demographic, clinical and therapeutic variables, as well as the origin and the evolution of cases were drawn from the cholera data base of the Tcholliré Health District. Data analysis was done using SPSS and Excel software. Between the 27th and 40th epidemiological weeks, 334 cases of cholera were notified in the Tcholliré Health District. The sex ratio was 1.27 (187M/147W), the men were most infected (56%). The mean age was 28±17 years, youths aged 16 to 34 were the age group that were most affected with 42.20%. The number of cases varied significantly based on the sex ratio and the health area (p = 0.012). The rate of relapse was 0.61 % and the mortality rate was 1.2%. All the patients had watery stools and vomiting. In addition, all patients were treated primarily with intravenous normal saline at 0.9% or Ringer Lactate and ORS for oral therapy. The antibiotic used was Doxycycline 100 mg. Cholera remains a diarrheal disease that threatens all regions in Cameroon. It comes about as a result of a deficiency in individual and collective hygienic practices, and a passive epidemiologic monitoring. Nevertheless, the institution of a monitoring system and also effective combat methods will significantly reduce the recurrence of cholera epidemics.